PENDAMPINGAN RELAYOUT PADA UMKM SEBLAK TANJAKAN - Dwi Auli Ramadhania; Putri Syfa Nadia; Sultan Additia Ramadhan; Wiji Safitri (BEGAWI : Jurnal Pengabdian Kepada Masyarakat, 2025)
MSMEs, especially in the culinary sector, play an important role in Indonesia's economy, but often face challenges in the form of sub-optimal business layouts, which impact operational efficiency and customer experience. Seblak Tanjakan, a culinary MSME owned by Ms. Novi, faces similar problems, such as lack of privacy in the dining area, confusing table layout, and inefficient access between areas. This service aims to increase operational efficiency, productivity, and business competitiveness through layout improvements. A process-oriented method is used through observation, in-depth interviews, and hands-on practice with business actors to find problems and offer solutions in designing a more efficient layout. The service team consists of three people who are Pelita Bangsa University students. The results of the assistance showed an improvement in workflow, a reduction in customer waiting time, and the creation of a more comfortable atmosphere through clear division of areas, ergonomic lesehan concepts, and smoother access between areas. The service received a very good assessment from the Seblak Tanjakan business owner. This service is expected to ensure sustainability of change, support business growth, and increase adaptability to market dynamics.